Self-assembled nanostructures of fully hydrated monoelaidin-elaidic acid and monoelaidin-oleic acid systems - Yaghmur, Anan (Langmuir : the ACS journal of surfaces and colloids, 2012)
In recent years, there has been a surge of interest in exploring the effect of trans-fatty acids (TFAs) on biological membrane properties. The research studies are motivated by an increasing body of evidence suggesting that the consumption of TFAs increases the risk of developing negative health effects such as coronary heart disease and cancer. The ultimate goal of studying the lipid-fatty acid interactions at the molecular level is to predict the biological role of fatty acids in cells. In this regard, it is interesting to elucidate the effect of loading TFAs and their counterpart cis-fatty acids (CFAs) on the physical properties of lipid model membranes. Here, the present study focuses on discussing the following: (1) the effect of mixing monoelaidin (ME, TFA-containing lipid) with its counterpart monoolein (MO, CFA-containing lipid) on modulating the fully hydrated self-assembled structure, and (2) the influence of solubilizing oleic acid (OA) and its trans counterpart elaidic acid (EA) on the fully hydrated ME system. The ME model membrane was selected due to its sensitivity to variations in lipid composition and temperature. Synchrotron small-angle X-ray scattering (SAXS) was applied for studying the temperature-dependent structural behavior of the fully hydrated ME/MO-based system prepared with an equal ME/MO weight ratio and also for characterizing the fully hydrated OA- and EA-loaded ME systems. Wide-angle X-ray (WAXS) experiments were also performed for characterizing the formed crystalline lamellar phases at ambient temperatures. The results demonstrate the significant influence of the partial replacement of ME by MO on the phase behavior. The addition of MO induces the lamellar-nonlamellar phase transitions at ambient temperatures and promotes the formation of the inverted type hexagonal (H(2)) phase above 72 °C. The fully hydrated ME/EA and ME/OA systems with their rich polymorphism exhibit an interesting temperature-dependent complex behavior. The experimental findings show that the temperature-induced phase transitions are dictated by the solubilized fatty acid concentration and its configuration. Both EA and OA have a significant impact on the fully hydrated ME system. Similar to previous published studies, OA induces a significantly stronger mean negative membrane curvature as compared to EA. The two phase diagrams are discussed in terms of water-lipid and lipid-fatty acid interactions, membrane bending, and lipid packing concepts. A newly observed interesting epitaxial relationship for the lamellar-hexagonal phase transition in the EA-loaded ME system is illustrated and discussed in detail